Representaciones del tema de la locura en cuentos selectos de Edgar Allan Poe - López Zurita, Marshury Lisbeth (2026)
Madness is a recurring theme in literature, but it has been little studied in Edgar Allan Poe’s short stories, despite his being widely recognized for presenting the sinister and the macabre in his narratives. This fact motivated the present research, which aimed to determine how the theme of madness is represented in two selected stories by the writer considered a master of the short tale: The Black Cat and The Tell-Tale Heart. The study analyzed madness by examining the protagonists’ behavior, their irrational obsession with certain objects and animals, and the decline of their sanity throughout each narrative. This research employs a qualitative approach and a bibliographic design; furthermore, hermeneutics is used to interpret the selected excerpts through content analysis. Madness serves as the central narrative axis in both stories. In The Black Cat, madness is unleashed by the influence of alcoholism; the narrator-protagonist becomes progressively aggressive until he ultimately loses all empathy, an innate human trait. In The Tell-Tale Heart, the narrator displays paranoia and hallucinations from the beginning of the text. After comparing these two stories, it becomes clear that both contain a symbolic representation of madness and an irrational obsession that drives the protagonists to become murderers, and in the end, their own paranoia betrays them to the authorities.